The importance of tobacco by a life partner - the opinions of students - Bieniak, Monika; Michałowska, Małgorzata; Mycek, Anna; Rząca, Marcin Stanisław; Bartoszek, Agnieszka; Charzyńska-Gula, Marianna (Journal of Education, Health and Sport, 2017)
Introduction: Habits learned in youth translate into behaviours in later stages of life. Systematically since 1995 percentage of smoking Poles has decreased. The most smokers decreased in group of pupils and students-almost half of them. Actually in Poland 33 % of men and 24% women smoke. Aim: Attitude of students of Universities and their partners to nicotine addiction. Materials and methods: In research took part 359 students of Lublin and Rzeszów Universities. Method used in research was diagnostic survey and the tool was author’s survey questionnaire. Results: Among examined group of students currently 13% women and 20% men smoke actively, 73% women and 59% has never smoked. 13% of respondents has smoking partner and 46 % non-smoking partner. Smoking tobacco by candidate for constant partner has very significant meaning for 65% respondents, little for 26%, and doesn’t matter for 9 % of respondents. Conclusion: Currently, tobacco is smoked most frequently by students of technical Universities, the least of Medical Universities. Smoking tobacco by current partner is the most significant for students of medical Universities. Smoking tobacco by candidate for permanent partner is more restrictively treated than smoking by current partner among students. Key words: smoking tobacco, partner, health behaviour